2020
DOI: 10.1097/olq.0000000000001231
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated With HIV and Sexually Transmitted Infections Among Female Sex Workers in Bamako, Mali

Abstract: We found a high prevalence of HIV and other STIs among female sex workers in Bamako, Mali. Contrary association with age and number of clients were observed for these outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Unexpectedly, we noted an inverse association between the high number of sexual partners and HPV infections. This is probably due to the high HIV prevalence among FSWs with < 5 clients as observed in our data publish elsewhere [25].…”
Section: Plos Onesupporting
confidence: 71%
See 1 more Smart Citation
“…Unexpectedly, we noted an inverse association between the high number of sexual partners and HPV infections. This is probably due to the high HIV prevalence among FSWs with < 5 clients as observed in our data publish elsewhere [25].…”
Section: Plos Onesupporting
confidence: 71%
“…These NGOs are the most active in the field of STI/HIV prevention in Mali, with a recognized leadership and trusted by FSWs. The details of NGOs from Mali are shown in a previous publication [25]. In Benin, we collaborated with "Santé et Développement (SED)", a NGO working with FSWs for over 20 years with confirmed proficiency in STI/HIV prevention and "SOLIDARITÉ", the local association of women practicing sex work, which operates a network of peer-educators (PEs).…”
Section: Study Design and Settingsmentioning
confidence: 99%
“…At each visit, a structured questionnaire was administered face-to-face by qualified interviewers. Data on sociodemographic, behavioral and sex work characteristics were collected, as well as obstetrical and reproductive history (see previous papers for more details (Tounkara et al 2020a, Tounkara et al 2020b. Each visit also included gynecological examination, vaginal and cervical swabs collection for curable STI testing.…”
Section: Data Collectionmentioning
confidence: 99%
“…All women were screened for abnormal cervical lesions using visual inspection with acetic acid and Lugol's iodine (VIA/VILI). A venous blood sample (3 ml) was collected for HIV testing (see previous papers for more details on storage process and banking of specimens (Tounkara et al 2020a, Tounkara et al 2020b.…”
Section: Data Collectionmentioning
confidence: 99%
“…Tounkara, et al [144] reported that overall HPV prevalence rates in Mali and Benin were 81.4% and 95.5%, respectively. Again, the top three high risk HPV genotypes in Mali were HPV-52 (12.9%), HPV-51 (14.3%) and HPV-16 (15.7%) whereas that of Benin was HPV-52 (28.8%), HPV-16 (36.6%) and HPV-58 (37.5%).…”
Section: Hpv Prevalence In Africamentioning
confidence: 99%